Energy and Nutrients of Iseilema laxum Hack., A Perennial Grass of Multiple Importance from Ravineland of Chambal Command at Morena (M.P), India - Sharma, D.P. (Asian Journal of Chemistry, 2010)
Iseilema laxum Hack. is a tufted perennial, drought resistant grass frequently appearing in monsoon season on slopy habitat of ravineland in Chambal Command area of Madhya Pradesh, India. This grass is widely used as feed for livestock, especially for horses. It exhibits a peak of 4286.40 cal/g of energy, 14.25% crude protein in November. Highest phosphorus 0.187% in September and 3.70% potassium in August.